Respostas
respondido por:
0
a)5 x² - 2 = 0
5 x² = 2
x² = 2/5
x = √2/5
b)(√2/3).x² = 0
x² = 0 / √2/3
x² = 0
x = √0
x = 0
c)x² + x/5 = 0
m.m.c = 5
5 x² / 5 + x / 5 = 0/5 eliminar o denominador
5 x² + x = 0
x(5 x + 1 ) = 0
x = 0
5 x + 1 = 0
5 x = - 1
x = -1/5
5 x² = 2
x² = 2/5
x = √2/5
b)(√2/3).x² = 0
x² = 0 / √2/3
x² = 0
x = √0
x = 0
c)x² + x/5 = 0
m.m.c = 5
5 x² / 5 + x / 5 = 0/5 eliminar o denominador
5 x² + x = 0
x(5 x + 1 ) = 0
x = 0
5 x + 1 = 0
5 x = - 1
x = -1/5
adlizinha2014:
Obrigada pela melhor resposta
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás